D. Weber correspondence - Weber, D. (Naturalist)
Letter relating to a naturalists' society.
Naturalist.
Collection material in German.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Naturalists -- Societies, etc; Naturalists